Middle East and North Africa Regional Economic Update, April 2012 : Enabling Employment Miracles - World Bank (Washington, DC, 2017)
Political uncertainties in the Middle East and North Africa (MENA) continue to affect the short term economic prospects in the region, while major developments in the global economy over the past six months have put the region on a two-track growth path for 2012. These developments include a significant rise in crude oil prices on fears of oil supply disruptions and weak economic activity in the Eurozone. Economic growth of MENA's oil exporting countries will be strong as it rebounds from the average of 3.4 percent in 2011 to 5.4 percent in 2012. Overall growth in the region is expected to be 4.8 percent in 2012, surpassing the 3 percent growth achieved in 2011. Improvement in the growth prospects of oil exporters is due to strength in oil markets. The fiscal situation is expected to remain tenuous for oil importing countries, especially those going through transitions. Overall, inflation is expected to remain subdued in 2012, with the notable exceptions of Iran and Egypt. Subsidies are currently dampening currently dampening the effects of increased global food and energy prices in many MENA countries.